Hambatan Penyidik Kepolisian Daerah Nusa Tenggara Timur dalam mengungkapkan Tindak Pidana Perdagangan Orang - Djo, Marlin; Manuain, Orpa G; Fanggi, Rosalind Angel (Law Faculty, Nusa Cendana University, 2024)
This research analyzes the obstacles faced by investigators from the East Nusa Tenggara Regional Police (Polda NTT) in uncovering criminal acts of human trafficking (TPPO), which is a serious and widespread problem in this region. TPPO often involves organized crime networks and complex modus operandi, such as document falsification and exploitation of victims' vulnerable positions. This research uses an empirical juridical approach and qualitative descriptive analysis techniques, with primary data obtained through interviews with investigators and secondary data from related literature. The research results show that the main obstacles facing the disclosure of TPPO include limited human resources, minimal special training for investigators, limited technology and infrastructure, and low public awareness of TPPO. Efforts to overcome these obstacles include increasing training for investigators, collaborating with relevant institutions, and public awareness campaigns about the dangers of human trafficking. This research provides recommendations for increasing the effectiveness of handling TIP in the NTT Regional Police through increasing investigator capacity and synergy between institutions.